Roman national ou récit féminin? La littérature des femmes pendant la Révolution tranquille - Boisclair, Isabelle (Globe, 1999)
Bien que l’on situe habituellement l’émergence du mouvement de l’écriture des femmes au milieu des années 1970, la production littéraire des femmes connaît une hausse importante en 1961 et la majorité de ces oeuvres, à l’instar de celles des hommes, participent d’un mouvement d’émancipation. Une relecture au féminin permet de déceler la portée contestataire contenue dans les oeuvres des femmes dès le début des années soixante. Durant la Révolution tranquille, pendant que les écrivains élaborent le « roman national », les femmes écrivent le « récit féminin ». Si l’écriture masculine tente d’affirmer sa québécitude et de s’émanciper du colonialisme, l’écriture des femmes tente d’affirmer sa spécificité sexuelle et de s’émanciper du patriarcat. Toutefois, les instances de réception critique ne perçoivent pas cette voix divergente, tout occupées qu’elles sont à détecter les signes de l’affirmation nationale.
Keywords: 1900-1999; 1960-1969; amériques; approches et analyses; arts; canada; cours; discipline; lit3495; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Ideología argentina (Universidad Nacional de Quilmes), 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty--and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Histoire des femmes en Occident - Duby, Georges; Perrot, Michelle (Plon, 1991)
Projet démesuré que de couvrir près de vingt siècles d'histoire du monde antique gréco-romain, de parcourir un espace qui va des rivages de la Méditerranée à ceux des mers du Nord, des colonnes d'Héraklès aux rives de l'Indus, de se plonger dans des documents aussi divers que les tombes d'une nécropole, la stèle inscrite plaquée aux murs du sanctuaire, le rouleau de papyrus, la scène peinte sur la panse d'un vase... et une littérature grecque et latine qui, si elle n'a pas donné la parole aux femmes, a beaucoup parlé d'elles. On l'aura deviné, ce livre n'a pas pour fonction de remplacer l'énorme production qui existe en ce domaine. Il aborde un petit nombre seulement des questions qui nous ont paru importantes pour aider à comprendre la place des femmes dans le monde antique et, plus encore peut-être, dans la perspective d'un ensemble de volumes traitant de l'histoire des femmes, comprendre les fondements d'habitudes mentales, de mesures juridiques, d'institutions sociales qui ont duré des siècles en Occident.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; antiquité; approches et analyses; conditions des femmes*; cours; discipline; europe; his4330; histoire; histoire des femmes*; histoire et politique; incontournable; lit3220; moyen-âge; occident; oui; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Idola Saint-Jean et le radicalisme féministe de l’entre-deux-guerres - Lamoureux, Diane (Recherches féministes, 1991)
Les suffragistes nous semblent souvent de bonnes bourgeoises aux méthodes et aux idées surannées. Pourtant, le féminisme de l'entre-deux-guerres est aussi diversifié que le féminisme actuel. Il est utile d'analyser ce passé féministe dans le contexte du mouvement de réforme sociale de l'époque pour ensuite apprécier le radicalisme de la pensée politique d'Idola Saint-Jean, une pensée politique marquée au coin de la justice sociale, de la démocratie et d'un sens aigu de l'antagonisme entre les sexes qui conditionne son activité militante
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; discipline; droit de vote; droits des femmes*; histoire et politique; justice sociale; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; suffragettes; thématiques

Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture,, 1989)
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

« La maternité refusée » dans La norme et les déviantes: des femmes au Québec pendant l'entre-deux-guerres - Lévesque, Andrée (La norme et les déviantes: des femmes au Québec pendant l'entre-deux-guerres, 1989)
Etude socio-historique des comportements sexuels de la femme au Québec sur une période de vingt ans. Les trois premiers chapitres traitent de la norme sociale qui s'impose aux femmes par rapport à la maternité et à la sexualité. Le reste concerne diverses formes de déviance sociale par rapport à trois catégories de comportements : le refus de la maternité (contraception, avortement, infanticide, abandon d'enfants); la maternité en dehors du mariage (mères célibataires); la sexualité commercialisée (prostitution).
Keywords: amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; cours; discipline; famille; his4523; histoire; hétérosexualité; justice reproductive; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sofia; thématiques

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach--in which pornography is defined as sex discrimination and therefore a violation of civil rights--would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance--what it is, what it does, what it means, how it works. Answers to the lies about it--lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." --from Pornography and Civil Rights
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Le Bordel: Milieu De Travail Contrôlé - Lévesque, Andrée (Labour / Le Travail, 1987)
PENDANT LONGTEMPS, des milliers de femmes gagnèrent leur vie dans des bordels à Montréal. L'étude de leur milieu de travail pendant les années vingt et trente révèle une organisation hiérarchique et des conditions dont le contrôle échappait aux principales intéressées. L'appareil judiciaire et policier, les organisations de réformes sociales, le clergé et les médecins hygiénistes affectaient, par la tolérance ou la répression, le cadre dans lequel s'exerçait la prostitution. Plus directement, les souteneurs, les tenancières et leurs gérantes déterminaient les conditions quotidiennes de travail. Les changements observés pendant toute cette période sont plus imputables à la vigilance policière qu'aux fluctuations économiques ou aux efforts des travailleuses elles-mêmes.
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; montréal; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; thématiques; travail; travail du sexe; travail du sexe-prostitution

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Pleasure and danger: Exploring female sexuality - Vance, Carole S. (Routledge & Kegan Paul, 1984)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality - Vance, Carole S. (Pleasure and danger: exploring female sexuality, 1984)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Studies on the history of Quebec, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Notes from the Second Year: Women's Liberation. - Firestone, Shulamith; Koedt, Anne (Women’s Liberation Movement Print Culture, 1970)
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; archives; cours; discipline; militance; patriarcat; pol5480; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; états-unis

The politics of housework - Mainardi, Patricia; New England Free Press (New England Free Press, 1970)
Keywords: 1900-1999; 1970-1979; amérique du nord; amériques; approches et analyses; care; cours; discipline; féminisme marxiste; histoire et politique; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis